Ideology and Private Law: Polish Experiences in the Long 20th Century - Machnikowska, Anna, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
This book highlights the ideological aspects influencing the modern shape of private law in Central and Eastern Europe (CEE), examining Poland as a representative example given the shared historical trajectory of the 20th century across this region. In the historico-legal literature currently in international circulation, there is a dearth of studies on the development of modern positive law in CEE countries. This volume therefore aims to bridge this gap and deliver a more profound reflection on the long-term social, economic, and political role of private law in this region.